Model Pembelajaran Drill And Practice untuk Meningkatkan Kualitas Pembelajaran Bahasa Inggris Materi Expression Of Congratulations pada Siswa Kelas IX B Di SMP Negeri 2 Bangsalsari Jember - Prayogo, Eko Rahmad (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the improvement of the quality of English learning in Expression of Congratulations material through the use of drill and practice learning models for class IX B semester 1 students at SMPN 2 Bangsalsari Jember for the 2018-2019 school year. The research design used is classroom action research in two cycles. Each cycle consists of planning, action, observation and reflection. The data collection method uses the method of observing student activities and learning outcomes tests. The conclusion of this study is that the use of the drill and practice learning model can improve the quality of English learning for Expression of Congratulations for class IX B students at SMPN 2 Bangsalsari Jember in the 2018-2019 semester 1 academic year. The indicator is an increase in student activity and learning outcomes. Student activity increased from the first cycle with a percentage of 69.7% with a good category increasing to 87% with a very good category, while student learning outcomes increased from the first cycle the average value of 74.35 with a percentage of completeness of 73.91% increased in cycle II to 84.57 with a percentage of completeness of 95.65%.